2020
DOI: 10.1021/acs.macromol.0c01383
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Design of Molecular Weight Distribution in Controlled Polymerization via a One-Pot Reaction Strategy

Abstract: Synthesizing polymers with tailor-made molecular weight distribution (MWD) is an essential step toward better control and design of functional polymer materials. We propose a novel one-pot reaction strategy that can facilitate the inverse design of the shape, breadth, and skew of the MWD in a controlled polymerization. By a multistep initiator addition scheme that involves a sequence of addition operations with determined amounts of initiators and addition times, the polymers with target MWD can be possibly sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…In principle, by shifting the LAM phase boundary toward higher volume fractions of hard block, one would enable the production of remarkably stiff, strong, and tough TPEs without compromising their elastomeric properties. Given the numerous accounts that have reported tuned phase behavior through varying block dispersity, 26–42,45,74–76 we sought to influence phase behavior and thereby tensile properties through controlling MWD skew.…”
Section: Influence Of Mwds On Thermoplastic Elastomersmentioning
confidence: 99%
See 2 more Smart Citations
“…In principle, by shifting the LAM phase boundary toward higher volume fractions of hard block, one would enable the production of remarkably stiff, strong, and tough TPEs without compromising their elastomeric properties. Given the numerous accounts that have reported tuned phase behavior through varying block dispersity, 26–42,45,74–76 we sought to influence phase behavior and thereby tensile properties through controlling MWD skew.…”
Section: Influence Of Mwds On Thermoplastic Elastomersmentioning
confidence: 99%
“…On this basis, a variety of methods for gaining synthetic control over polymer MWDs have been developed 15–46 . Although the majority of early methods only afforded control over the relative breadth of the MWD, a limited number for controlling the entire MWD have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although low dispersity polymers ( Đ <1.20) were initially the preferred target for polymer chemists, [10–12] it has recently been demonstrated that moderate ( Đ =1.20–1.50) and high dispersity ( Đ >1.50) materials are equally desirable and exhibit complementary properties and characteristics [7, 13–16] . This has resulted in the development of various chemistry and engineering methods to target different dispersity values and to tailor MWD shapes [3, 8, 17–22] …”
Section: Introductionmentioning
confidence: 99%
“…14,16,17 Other noticeable examples include blending approaches, 9,18 data encryption via MWD fingerprints developed by the Junkers group, [19][20][21][22] and the use of elegant flow chemistry methods employed by the groups of Frey, Boyer, Leibfarth, Guironnet, and Lu. [23][24][25][26][27][28][29] The vast majority of these methodologies include the design of suitable equations and modelling systems to precisely tailor MWDs and provide polymers with a high range of Ɖs.…”
mentioning
confidence: 99%